2012
DOI: 10.1002/jcb.24197
|View full text |Cite
|
Sign up to set email alerts
|

The synthetic purine reversine selectively induces cell death of cancer cells

Abstract: The synthetic purine reversine has been shown to possess a dual activity as it promotes the de-differentiation of adult cells, including fibroblasts, into stem-cell-like progenitors, but it also induces cell growth arrest and ultimately cell death of cancer cells, suggesting its possible application as an anti-cancer agent. Aim of this study was to investigate the mechanism underneath reversine selectivity in inducing cell death of cancer cells by a comparative analysis of its effects on several tumor cells an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 37 publications
(69 reference statements)
1
7
0
4
Order By: Relevance
“…As a strategy for dual inhibition of AURKA and AURKB, reversine [2-(4-morpholinoanilino)-6-cyclohexylaminopurine] was employed. Reversine is a small synthetic purine analogue that induces mitotic catastrophe, cell-cycle arrest, polyploidy, and apoptosis in several cancer models 1619 . Herein, we described the molecular and cellular effects of the treatment with reversine in the context of JAK2 V617F -positive MPN.…”
Section: Introductionmentioning
confidence: 99%
“…As a strategy for dual inhibition of AURKA and AURKB, reversine [2-(4-morpholinoanilino)-6-cyclohexylaminopurine] was employed. Reversine is a small synthetic purine analogue that induces mitotic catastrophe, cell-cycle arrest, polyploidy, and apoptosis in several cancer models 1619 . Herein, we described the molecular and cellular effects of the treatment with reversine in the context of JAK2 V617F -positive MPN.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, this protein has emerged as a potential target for cancer therapy and reversine is known to inhibit Mps1 more efficiently than Aurora-B kinase, based on experimental and computational approaches [ 9 ]. As inhibitor of Aurora-A and Aurora-B kinases and Mps1, reversine causes an incorrect mitotic spindle assembly and chromosome separation, cell cycle arrest in G2/M phase, endoreduplication and eventually cell death due to a phenomenon called “mitotic catastrophe” observed in many cancer cell lines [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. Moreover, reversine treatment of human follicular thyroid cancer cells leads to the activation of autophagy due to its capability to down-regulate mTOR [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…p53 has been observed to play an important role in modulation of reversine effect. It has been demonstrated that silencing of p53, and the consequent loss of transcriptional activation of its target p21, whose checkpoint function can prevent endoreduplication, renders fibroblasts more sensitive to reversine [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The interference raised by Rev with the mitotic spindle organization is described to block cells mainly in the G 2 /M (Chen et al, ) and G1/S transitions (Piccoli et al, ). We also confirmed this assumption for OA chondrocytes by quantitative RT‐PCR experiments, assessing the Ki67 and cyclin D1 mRNA levels.…”
Section: Resultsmentioning
confidence: 99%